Synthesis of calcite-based bio-composite biochar for enhanced biosorption and detoxification of chromium Cr (VI) by Zhihengliuella sp. ISTPL4. (July 2020) - Mishra, Arti; Gupta, Bulbul; Kumar, Naveen; Singh, Rashmi; Varma, Ajit; Thakur, Indu Shekhar
Graphical abstract: Highlights: WGS of strain ISTPL4 reveals presence of Cr reductase and other candidate of genes. Freundlich and IPD isotherm model suggests no monolayer formation till 500 ppm of Cr. Immobilized enzyme on activated biochar with calcite showed 99% removal of the Cr. Toxicity of Cr (VI) was evaluated by MTT assay on HepG2 cell line. Abstract: The current study presents a comprehensive analysis of the potential of actinobacterium Zhihengliuella sp. ISTPL4 and different composite materials for the removal of hexavalent chromium [Cr (VI)]. Genome analysis of strain indicated the presence of several oxidoreductases which includes chromate reductase, nitrate reductase, thioredoxin, superoxide dismutase and hydrogenase are other major candidate genes. Catalytic calcite-based bio-composite material was absorbed on biochar had highest Cr removal efficiency. The main mechanism involved in Cr biosorption by this strain was explained by the Langmuir isotherm model; under equilibrium conditions the maximum adsorption was observed 49 ± 0.3 mgg −1 . Kinetic studies showed that biosorption of Cr (VI) by this strain was a rate-limiting step and followed a pseudo-second-order kinetics (R2 = 0.99). SEM analysis is in line with EDX result indicating highest Cr removal by calcined biochar. MTT assay shown that the bacteria successfully convert toxic Cr (VI) to comparatively less toxic form such as Cr (III).